ANALYSIS OF RESIDENTIAL ENVIRONMENT AND ENERGY USE IN RURAL AREAS IN HOT SUMMER AND COLD WINTER REGION OF CHINA-A CASE STUDY OF HANGZHOU - Jiang Lu; Jian Ge; Xiao Yu Luo; Min Yan Lu (Lowland Technology International, 2014)
With the gradual development of the new rural construction, and the continuous improvement of the rural per capita living space, sustainable development of the rural living environment is becoming an increasingly urgent task. This paper selected three different terrain villages in the rural area of Hangzhou as a study object, which located in the Middle and lower reaches of Yangtze River. Firstly, the investigation, collection and analysis on the building status, energy data and residents’ subjective feeling of the three villages had been done through basic research and sampling questionnaire. Secondly, it selected two typical housing in each village, separately carried on the measurement of the building physical environment and computer quantitative simulation of the ventilation, lighting, and energy consumption, along with the comprehensive evaluation with the simulation results. Finally, the major existing problems of the living environment in the rural areas have been found, according to which some operable implementation strategy and policy Suggestions have been put forward.